Impact of facial deformity on the patient's perception in orthodontic treatment: A case-control study (Research, Society and Development, 2021)
This study evaluated the impact of facial deformity on pain perception of patients undergoing orthodontic and orthodontic-surgical treatment. A case-control study was carried out with a population-based of individuals in orthodontic treatment. Cases and controls were defined by the Oral Health Impact Profile (OHIP-14). The case group (n=54) included individuals who responded “never” to at least one of the questions, and in control (n=44), those who responded “rarely and sometimes” frequently and “always” to both questions. Cases and controls were paired by sex, age, and clinical conditions in the ratio of 1:1. For data analysis, the odds ratios were estimated with respective confidence intervals of 90%. There was no significant difference between the groups with and without deformities relative to the distribution of the female and male sexes (p=1.000), which allowed pairing the case and control groups in a ratio of 1: 1. Patients with facial deformity showed 2.14 (CI90%: 1.08-4.24) times more chance of reporting the impact on physical pain (p=0.0662). Patients with a facial deformity and orthodontic surgical treatment are twice as likely to perceive physical pain.